ANALISIS PROGRAM PERCEPATAN DAN PERLUASAN PEMBANGUNAN INFRASTRUKTUR PERMUKIMAN (P4IP) BERBASIS PEMBERDAYAAN MASYARAKAT DI KOTA PADANGSIDIMPUAN PROVINSI SUMATERA UTARA - Ris Artalina Tampubolon; Jenny Yelina Rambe (Institut Pendidikan Tapanuli Selatan, 2023)
Communities as one of the main elements in development today are increasingly required to participate. This research is important as an example of a program study whose management is based on community empowerment to encourage commitment and partisanship of the government in establishing policies for poverty reduction efforts with a participatory development pattern. Because the management of community empowerment-based programs is very different from programs whose management is not based on community empowerment. This study aims to analyze the implementation of the Settlement Infrastructure Development Acceleration and Expansion Program and see the government's efforts in empowering the community to answer the main problems of Padangsidimpuan city development. Theoretically. The research method is carried out through descriptive analysis, which is a fact finding method with the right interpretation. This descriptive analysis focuses on the problems that existed at the time the research was carried out which were actual and described the facts about the problem being investigated as they were, accompanied by a strong rational interpretation. The results showed that, Based on the results of data analysis for each variable, it was concluded that the implementation of the Community Empowerment-based Acceleration and Expansion of the Settlement Infrastructure Development Program in Padangsidimpuan City was very effective, this can be seen from the results of respondents' answers on the effectiveness variable, where the percentage obtained is equal to 86.06% and is in the